2019
DOI: 10.14295/2238-6416.v74i1.729
|View full text |Cite
|
Sign up to set email alerts
|

Nisin reduces the Staphylococcus aureus count without changing the characteristics of artisanal Minas cheese from Araxá

Abstract: O queijo tradicional de Araxá é produzido com leite cru, o que representa um risco para a saúde dos consumidores. A ação da nisina (100 UI/g e 400 UI/g) contra Staphylococcus aureus durante a maturação de Queijos Minas Artesanais de Araxá foi avaliada e a nisina reduziu a contagem de S. aureus para menos de 1 log UFC/g do começo ao fim da maturação. A nisina aumentou ligeiramente o pH e o teor de umidade e diminuiu o teor de gordura do Queijo Minas Artesanal de Araxá; no entanto, com a menor concentração de ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since being recognized as food safety in 1969, nisin has been used as a natural preservative in various foods, such as cheese, dairy products, various pasteurized dairy products, high moisture, hot baked flour products (crumpets), and canned foods (De Arauz et al, 2009;Delves-Broughton et al, 1996). Sobral et al (2019) found that during the entire ripening process of cheese, adding 100 IU/mL of nisin could continuously reduce the number of S. aureus below 1.5 log10 CFU/g, greatly reducing the risk of consumption of enterotoxins without altering the characteristics of cheese. Because of its bacteriostasis, safety, and no impact on the sensory properties of food, researches on the preservation effect of nisin in various foods, such as beverages, fruits and vegetables, and meat, have not stopped (Table 5).…”
Section: Application In Food Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Since being recognized as food safety in 1969, nisin has been used as a natural preservative in various foods, such as cheese, dairy products, various pasteurized dairy products, high moisture, hot baked flour products (crumpets), and canned foods (De Arauz et al, 2009;Delves-Broughton et al, 1996). Sobral et al (2019) found that during the entire ripening process of cheese, adding 100 IU/mL of nisin could continuously reduce the number of S. aureus below 1.5 log10 CFU/g, greatly reducing the risk of consumption of enterotoxins without altering the characteristics of cheese. Because of its bacteriostasis, safety, and no impact on the sensory properties of food, researches on the preservation effect of nisin in various foods, such as beverages, fruits and vegetables, and meat, have not stopped (Table 5).…”
Section: Application In Food Fieldmentioning
confidence: 99%
“…Sobral et al. (2019) found that during the entire ripening process of cheese, adding 100 IU/mL of nisin could continuously reduce the number of S. aureus below 1.5 log10 CFU/g, greatly reducing the risk of consumption of enterotoxins without altering the characteristics of cheese. Because of its bacteriostasis, safety, and no impact on the sensory properties of food, researches on the preservation effect of nisin in various foods, such as beverages, fruits and vegetables, and meat, have not stopped (Table 5).…”
Section: Application Of Nisinmentioning
confidence: 99%
“…NIS is a wellknown antimicrobial peptide that is produced commercially by certain strains of Lactococcus lactis spp. lactis, and employed in a great variety of food product such as cheeses (fresh, ripened and/or processed), pasteurized fluid egg products (egg yolk or white and whole eggs), desserts (e.g., cereal, starch, and dairy-based desserts), etc (Ahmadi, Soleimanian-Zad, & Sheikh-Zeinoddin, 2016;Kallinteri, Kostoula, & Savvaidis, 2013;Morsy, Sharoba, Khalaf, El-Tanahy, & Cutter, 2015;Oshima et al, 2014;Schuman, 1997;Silva, Silva, & Ribeiro, 2018;Smigic et al, 2018;Sobral et al, 2019). NIS shows antimicrobial activity mainly on Gram-positive bacteria, but its mechanism of antimicrobial activity involves interaction with the anionic phospholipids at the bacterial surfaces and formation of pores, and dissipation of proton motive forces at the bacterial membrane (Sudagidan & Yemenicioglu, 2012).…”
Section: Introductionmentioning
confidence: 99%